The Effect of Green Accounting Implementation, Environmental Performance, and Sustainability Growth on Financial Reporting Quality with Profitability as A Moderating Variable - Herny, H.; Herawaty, Vinola (Golden Ratio of Finance Management, 2024)
The non-climatic sector is a sector that is directly related to nature, so the activities carried out will have an impact on the sustainability of the surrounding environment. If natural and environmental factors are appropriately considered, it will impact the quality of financial reporting. This study aims to test and analyze the Effect of green accounting, environmental performance, and sustainability growth on financial reporting quality with Profitability as the control variable in companies listed on the Indonesia Stock Exchange for 2021 - 2023. From the research conducted, it was found that green accounting does not affect the quality of financial reporting, environmental performance affects the quality of financial reporting, sustainability growth has no effect on the quality of financial reporting, and Profitability affects the quality of financial reporting.